PENGARUH KOMUNIKASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. BANK RAKYAT INDONESIA (Persero)Tbk. KANTOR CABANG LAHAT - Delvina Yulanda (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2021)
Employee performance is an important factor in the company, because it can determine the company’s success. Leadership styles can affect every employee in a company. Good communication can enhance good relations between colleagues. The style of leadership and communication can produce a good performance for the company’s employees. The purpose of this study is to determine the effect of communication and leadership styles on the performance of employees at PT. Bank Rakyat Indonesia (Persero)Tbk. Lahat Branch Office partially or simultaneously. 30 out of 30 population were taken as respondents. The research method using multiple regression analysis. The result of this study is the communication and style of leadership have a positive and significant effect either simultaneously or partially on employee performance. PT. Bank Rakyat Indonesia (Persero)Tbk. Lahat Branch Office should improve the communications process by building good communication network